Rethinking resilience: home gardening, food sharing and everyday resistance - Jehlicka, Petr; Danek, Petr; Vávra, Jan (Routledge journals, Taylor and Francis LTD., 2019)
Resilience and food self-provisioning (FSP), terms that until recently were deployed primarily in the study of livelihoods in the Global South, are now attracting attention from alternative food scholarship in the Global North. Drawing on a large-scale survey conducted in the Czech Republic, this article investigates FSP as a social resilience-enhancing set of practices. In addition to the traditional reading of FSP as a passive, defensive and crisis-deflecting form of resilience, this article puts forward an alternative conceptualisation of resilience as a proactive, preventative, future-oriented and transformation-enabling capacity that runs counter to the tenets of neoliberalism.
Keywords: Resilience; sharing; food self-provisioning; alternative food networks; food entitlements